Autologous Platelet Rich Plasma (PRGF) Preserves Genomic Stability of Gingival Fibroblasts and Alveolar Osteoblasts after Long-Term Cell Culture - Eduardo Anitua; María de la Fuente; María Troya; Mar Zalduendo; Mohammad Hamdan Alkhraisat (Dentistry Journal, 2022)
Plasma rich in growth factors (PRGF) has several applications in dentistry that may require repeated applications of PRGF. Furthermore, it has been used for ex vivo expansion of human origin cells for their clinical application. One of the most relevant issues in these applications is to guarantee the genetic stability of cells. In this study, the chromosomal stability of gingival fibroblasts and alveolar osteoblasts after long-term culture was evaluated. Cells were expanded with PRGF or foetal bovine serum (FBS) as a culture medium supplement until passage 7 or 8 for gingival fibroblast or alveolar osteoblasts, respectively. A comparative genomic hybridization (CGH) array was used for the genetic stability study. This analysis was performed at passage 3 and after long-term culture with the corresponding culture medium supplements. The cell proliferative rate was superior after PRGF culture. Array CGH analysis of cells maintained with all the three supplements did not reveal the existence of alterations in copy number or genetic instability. The autologous PRGF technology preserves the genomic stability of cells and emerges as a safe substitute for FBS as a culture medium supplement for the clinical translation of cell therapy.